A Framework for Benchmarking Energy Retrofit Systems through Building Information Modeling (BIM) - Elmani, Ahmad Hussein (2015)
A Master of Science thesis in Civil Engineering by Ahmad Hussein Elmani entitled, "A Framework for Benchmarking Energy Retrofit Systems through Building Information Modeling (BIM)," submitted in June 2015. Thesis advisor is Dr. Salwa Mamoun Beheiry. Soft and hard copy available.